IMPLEMENTASI PROGRAM KELOMPOK SADAR WISATA (POKDARWIS) DI KELURAHAN KANDRI, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Tiara Nur Tsofyani Putri; Hartuti Purnaweni; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Tourism is one of the national industry which have not thoroughly developed in Indonesia yet. In the efforts to developing Indonesia’s tourism which also related with increasing nation foreign exchange, the government establishing a tourism developing programme based on community empowerment called Kelompok Sadar Wisata (Pokdarwis). One of the oldest Pokdarwis in Semarang is Pokdarwis Pandanaran located in Kelurahan Kandri, Kecamatan Gunungpati, Kota Semarang which also the only Pokdarwis that can survive since established in 1993, so it’s interesting to see about how is the development process of the programme implementation and what is the not only motivating but also limiting factors in this implementation process. The purpose of this study is to learn about the programme implementation especially in Kelurahan Kandri including the motivating and limiting factors so the result can help to improve not only Pokdarwis Pandanaran but also other Pokdarwis. This study used a qualitative descriptive research method by using observation and interview to get the data. The result of the study itself is there are a linkage between the position, role and potency of the Kelurahan Kandri community with the improved quality of the programme implementation. The community are not an object of the implementation, but a subject, in that way, the community will feel the urge to participate to the programme because its correspond with their life, their consideration. Furthermore, the phenomenon of implementation from Van Meter and Van Horn theory, which is statutory goals and objective, programme’s environment and programme’s resources is included in the motivating and limiting factors to the implementation of Pokdarwis.